2018
DOI: 10.1140/epjc/s10052-018-5643-1
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Born–Infeld-like nonlinear electrodynamics using hydrogen’s ionization energy

Abstract: In this work, the hydrogen's ionization energy was used to constrain the free parameter b of three BornInfeld-like electrodynamics namely Born-Infeld itself, Logarithmic electrodynamics and Exponential electrodynamics. An analytical methodology capable of calculating the hydrogen ground state energy level correction for a generic nonlinear electrodynamics was developed. Using the experimental uncertainty in the ground state energy of the hydrogen atom, the bound b > 5.37 × 10 20 K V m , where K = 2, 4 √ 2/3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…When confronted with those obtained in low-energy experiments, as in [14], our constraints are up to 20 orders of magnitude lower for α = β. In [18] in which the effects of Born-Infeld-like theories were analyzed using the hydrogen's ionization energy, the lower bound b ≥ 1.07 × 10 21 V m −1 , corresponding to α = β ≤ 8.1 × 10 4 GeV −4 , is 14 orders of magnitude larger. Lastly, 12 orders of magnitude of precision were obtained when comparing the upper bound for the Born-Infeld parameter in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When confronted with those obtained in low-energy experiments, as in [14], our constraints are up to 20 orders of magnitude lower for α = β. In [18] in which the effects of Born-Infeld-like theories were analyzed using the hydrogen's ionization energy, the lower bound b ≥ 1.07 × 10 21 V m −1 , corresponding to α = β ≤ 8.1 × 10 4 GeV −4 , is 14 orders of magnitude larger. Lastly, 12 orders of magnitude of precision were obtained when comparing the upper bound for the Born-Infeld parameter in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this framework can be used to study arXiv:1809.01296v2 [hep-ph] 24 Jun 2019 how the modification of Coulomb's potential due to NLED affects the ground-state energy. Comparison with experimental results constrains the magnitude of these corrections and, consequently, the parameters of the theory [16][17][18]. It is noteworthy that the complete Lagrangian is needed in this procedure, which imposes a particular analysis for each theory.…”
Section: Introductionmentioning
confidence: 99%
“…(24) and (29), by making use of fiducial magnetar parameters [R = 10 km and M = 1.4 M ], it follows that |ε Ma | = 1.20× 10 −6 . Taking into account hydrogen experiment outcomes [26], one learns that the absolute minimum value for Born-Infeld's scale field is b min ≈ 3.96 × 10 15 statvolt cm −1 (or b min ≈ 3.96 × 10 15 G) [20] [most recent data for the mass and charge of the electron have been used]. Thus, from the above and Eqs.…”
Section: Possible Astrophysical Implications Of Born-infeld Magnetarsmentioning
confidence: 99%
“…It already has an exact black hole solution [see for instance 22, and references therein] though in this context singularities are unavoidable [23]. When applied to the hydrogen atom, Born-Infeld theory as the description for electromagnetic interactions meets the observational spectrum of this atom only if its scale factor b is larger than the one inferred by Born and Infeld themselves within the unitarian viewpoint [24][25][26], approximately 10 15 statvolt cm −1 (or also 10 15 G) [20] (around 100 times QED's critical fields [19]). There are also constraints on b coming from particle accelerators.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that compatibility of this NED in D = 4 with hydrogen's ionization energy allows to constrain the Born-Infeld parameter as µ −1 > 1.074 × 10 21 V /m; see[84] for details.…”
mentioning
confidence: 99%